2017
DOI: 10.1039/c7tb00929a
|View full text |Cite
|
Sign up to set email alerts
|

Novel PAN/PVP Janus ultrafine fiber membrane and its application for biphasic drug release

Abstract: Materials with Janus structures have attracted significant attention in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 35 publications
0
39
1
2
Order By: Relevance
“…Figure 2c showed the magnification of individual as-spun Janus nanofiber, which consisted of two semicylinder and a clear dividing boundary along the nanofiber axial direction on the nanofiber surface, because the two electrospinning precursor solutions had a matched viscosity. In our previous study and other findings indicated side-byside electrospinning can form Janus nanofibers when the following conditions were satisfied (1) the two electrospinning precursors had a similar viscosity [3], and (2) the time of nanofibers formation was faster than mixing between miscible electrospinning precursor solutions [21]. After carbonation, the as-spun Janus nanofibers were converted to CoO x /C Janus nanofibers, which embedded CoO x nanoparticles with a decrease in diameter to 300 ± 50 nm showed in Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure 2c showed the magnification of individual as-spun Janus nanofiber, which consisted of two semicylinder and a clear dividing boundary along the nanofiber axial direction on the nanofiber surface, because the two electrospinning precursor solutions had a matched viscosity. In our previous study and other findings indicated side-byside electrospinning can form Janus nanofibers when the following conditions were satisfied (1) the two electrospinning precursors had a similar viscosity [3], and (2) the time of nanofibers formation was faster than mixing between miscible electrospinning precursor solutions [21]. After carbonation, the as-spun Janus nanofibers were converted to CoO x /C Janus nanofibers, which embedded CoO x nanoparticles with a decrease in diameter to 300 ± 50 nm showed in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Nanofibers have a high specific surface area and their structure is controllable. Different unique structures can be prepared through the design of the needle and the choice of spinning solution, such as core-shell structure [1], hollow structure [2], Janus structure [3], porous structure [4], and necklace-like structure [5]. These unique structures can be used to prepare nanofibers with multiple functions.…”
Section: Introductionmentioning
confidence: 99%
“…The Janus pellicle is a novel pellicle with asymmetric properties on each part [1]. As one of the pellicle materials, Janus pellicles [2][3][4][5][6] have been widely used in electrical engineering and biology due to their special structural characteristics. For example, a PVFM-based Janus pellicle is used for a highly durable Li-O 2 battery [7], a bionic Janus composite pellicle is used for a smart response actuator [8], and a hydrophobic-hydrophilic Janus pellicle is used for the mist collector [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more and more researchers focus their attention on multifunctional composite materials. [9][10][11][12][13] In recent years, magnetic-uorescence bifunctional nanomaterials have been widely used in drug delivery and biomolecular detection. 14 For example, magnetic-uorescence bifunctional nanomaterials have important applications in the eld of drug delivery, because loaded drugs can be transferred to specic location via magnetic navigation.…”
Section: Introductionmentioning
confidence: 99%